Fatwa and The Development of Islamic Financial Industry: A Lesson From Indonesia - Ma'ruf Amin (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
This article is a critical study to analyze the impact of the Fatwa issued by Ulema of the Indonesian Ulema Council (MUI) against the Development of Sharia Financial Industry in Indonesia. The development of Sharia financial industry in Indonesia has been started since the early 1990s. But the most improved level of development was since 2003, when MUI issued a fatwa on the illegitimate Bank’s Interest. It was a necessity for the Ulema to perform ijtihad or istinbat laws in order to give a fatwa on his people. Ulema as the agents of social change oriented to make continuous improvements (islahiyyah) in the social -economic order, especially in the financial industry. Considering that the circulation of money in the community is a reflection of society, if the financial flows controlled by virtuous people then so the community. Conversely if the flows of finance are controlled by people who are not good, then the community became devastated.DOI: 10.15408/aiq.v9i2.5353